‘USYUR SEBAGAI KEBIJAKAN FISKAL PADA MASA KEKHALIFAHAN UMAR BIN KHATTAB - Andika Isma; Della Fadhilatunisa; Annisa Nabilah Hasan; Yunita Alfira Liadi; Sulfa Inriani (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This paper discusses descriptively 'usyur as a fiscal policy during the caliph Umar bin Khattab. 'usyur was one of the fiscal policies in the early days of Islam. The practice of 'usyur was first practiced during the time of Umar bin Khattab and had an impact on the welfare of the people. ‘usyur activities during the Islamic period were almost the same as the current customs practice. The purpose of this study is as a means of information to readers regarding taxation in the early Islamic period, especially 'usyur taxation during the time of Umar bin Khattab. This paper uses library research in collecting data and references related to the research title. The results of the study describe how Umar bin Khattab's system in determining 'usyur as a fiscal policy during his reign. In addition, it also explains how the relevance of 'usyur and customs is today.